Impact of adjuvant radiation therapy after definitive surgery in senior adults >80 years old with advanced head and neck squamous cell carcinoma on overall survival - Butkus, Joann M.; Crippen, Meghan; Bar-Ad, Voichita; Luginbuhl, Adam (Frontiers in Oncology, 2022)
Background: Adjuvant radiotherapy (RT) following surgical resection confers a survival benefit for adult patients with locally advanced head and neck squamous cell carcinoma (HNSCC). We aim to investigate if adjuvant RT provides a similar survival advantage to patients ages 80+ through a national curated database. Methods: This retrospective cohort study queried the National Cancer Database (NCDB) for all cases of HNSCC between 2004-2016. Patients treated with surgical resection alone were compared to those treated with surgery plus adjuvant RT. Overall survival (OS) was compared within adult (age 80 years) and senior adult (age 80 years) cohorts using Kaplan-Meier analysis. Hazard ratios (HR) were assessed using Cox proportional hazards to account for differences in patient characteristics, primary site, and HNSCC stage. Results: NCDB identified 16,504 locally advanced HNSCC treated with definitive surgery with 9,129 (55.3%) also receiving adjuvant RT. The mean age was 63.8 years (SD = 12.0) with 88.7% of patients ages <80 years and 11.3% ages 80 years. In the adult cohort, adjuvant RT was associated with a significant increase in OS compared to surgery alone at 1 year (88.4% vs. 83.8%, p=<0.001), 3 years (64.0% vs. 59.2%, p=<0.001) and 5 years (52.8% vs 47.2%, p=<0.001). Treatment with surgery alone remained a significant predictor of mortality risk at 1 year (HR 1.48, 95% CI 1.35-1.64, p<0.001), 3 years (HR 1.25, 95% CI 1.18-1.33, p<0.001), and 5 years (HR of 1.23, 95% CI 1.17-1.30, p=<0.001). In the senior adult cohort, there were no significant differences in OS between treatment groups at 1 year (73.4% vs. 74.8%, 0.296), 3 years (45.8% vs. 41.8%, p=0.465), or 5 years (28.2% vs. 27.7% p=0.759). Treatment with surgery alone was not a significant predictor of mortality risk at 1 year (HR 1.11, 95% CI 0.90-1.36, p=0.316), 3 years (HR 0.94, 95% CI 0.81-1.08, p=0.423), or 5 years (HR 0.95, 95% CI 0.83-1.08, p=0.476). Conclusion: The addition of adjuvant RT in senior patients (age 80 years) may not provide a similar OS benefit to that observed in younger patients. Further research is needed to best guide shared-decision making in this population.